Generation of THz signals based on quasi-ballistic electron reflections in double-heterojunction structures - Ong, D S; Hartnagel, H L (IOP PUBLISHING LTD, 2007)
The generation of THz signals by the periodic quasi-ballistic resonant motion of electrons on the basis of the combined action of electron acceleration in a potential well and reflection at the heterointerface is demonstrated by a Monte Carlo simulation. The electron dynamics in In0.52Al0.48As/In0.53Ga0.47As/In0.52Al0.48As heterostructures is investigated for different well widths and doping densities under the influence of fundamental-wave signals which conveniently can also be of square shape of 100 GHz and 200 GHz. It is found that the resulting quasi-ballistic electron motion produces oscillations within these wells which generate particularly high odd harmonics in the terahertz frequency range. Simulation results of this new type of resonance phenomenon show that the amplitude of the THz radiation strongly depends on the well width and voltage level of the square wave signal. This study shows that double-heterojunction structures with well width of ballistic electron transport length are promising candidates for the design of efficient THz sources.